Design improvement and analysis of mechanism system for newspaper vending machine - Radiah Binti Alizan (School of Materials Engineering, University Malaysia Perlis, 2010)
This project aims to solve the problem in the methods of selling and purchasing daily newspaper in Malaysia by giving a new idea of improvement and analysis of mechanism system in newspaper vending machine which operates automatically to vend a single of newspaper. By applying the step in design process, a few ideas of concepts have been generated and evaluated by using screening and scoring method to get the best concept to be developed. Next, a series of analysis have been selected. Few drawings also have been made before proceed to the stage of prototype making. From the result of the research, a mechanism of newspaper vending machine that vends a single copy of newspaper at one time has been designed. The design has solved the problems stated and then achieved the objective of the project.